A sodium ion energy storage battery

By using Prussian blue and titanium-based materials in sodium ion batteries and designing coordination crosslinked gel polymer electrolytes, the challenges of sodium ion batteries in comprehensive performance, safety and cost are solved, and a low-cost, long-life, and high-safe high-performance sodium ion energy storage battery is achieved.

CN119230919BActive Publication Date: 2025-02-28BENAN ENERGY TECH JIANGSU CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411723950.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Sodium ion batteries have challenges in integrating battery performance, safety and cost, including issues of energy density, cycle life, cycle stability, safety and production costs.

Method used

Prussian blue material is used as the positive electrode active material and titanium-based material is used as the negative electrode active material. A coordination crosslinked gel polymer electrolyte is designed to build a high-performance sodium ion energy storage battery through the combination of polymer network and bifunctional inorganic filler.

Benefits of technology

It realizes the low cost, long life and high safety characteristics of sodium ion energy storage batteries, and significantly improves their performance under high magnification conditions, meeting the prospects of commercial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230919B_ABST
    Figure CN119230919B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion energy storage battery, which belongs to the technical field of battery preparation. The sodium ion battery system of the invention includes a Prussian blue positive electrode material, a titanium-based negative electrode material and a gel electrolyte, wherein the gel electrolyte contains an electrolyte and an electrolyte carrier, wherein the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer; wherein the inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded in the sodium titanium phosphate carrier, and the metal salt contains an iron salt. The electrolyte preparation process is simple and the raw material resources are abundant. The functional filler is prepared by adsorbing the metal salt on the sodium titanium phosphate carrier, the ion transmission is regulated, the ion conductivity and the ion migration number are improved, and at the same time, with the appropriate negative electrode material, the cycle life and rate performance of the Prussian analog in the electrolyte can be effectively extended, thereby improving the application value of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium ion energy storage battery, belonging to the technical field of batteries. Background Art

[0002] As a typical secondary energy storage battery, lithium-ion battery has the characteristics of high energy density and low self-discharge, and is widely used in various fields of life. The working principle of lithium-ion battery is similar to that of sodium-ion battery. With its low price and abundant reserves, sodium-ion battery is expected to become a supplement to lithium-ion battery. As an emerging energy storage technology, although sodium-ion battery has potential advantages in resource abundance and cost, it still faces some difficulties and needs in its industry development process: 1) Improvement of comprehensive battery performance: including energy density, cycle life and cycle stability. The comprehensive battery performance of sodium-ion batteries is currently lower than that of lithium-ion batteries, which limits its competitiveness in certain high-energy density applications (such as electric vehicles). Large-scale energy storage faces the research and development application goals of "low cost, long life, high safety, and easy recycling". Therefore, sodium-ion batteries need to develop new electrode materials, battery designs and electrolyte systems to meet the above requirements; 2) Safety and reliability: Like all battery technologies, the safety and reliability of sodium-ion batteries are key issues, especially in large-scale energy storage applications. In the design of battery systems, it is necessary to develop safer electrolytes and battery structures to fundamentally achieve an intrinsically safe battery system; 3) Cost reduction: Although sodium resources are abundant, the production cost of sodium-ion batteries is still high, especially in the initial R&D and large-scale production stages. It is necessary to start from the top-level design and reduce production costs through large-scale production and process optimization. This includes the selection of positive and negative electrode materials, as well as the design of electrolytes.

[0003] At present, the research on positive electrode materials of sodium ion batteries mainly focuses on three types: layered transition metal oxides, Prussian blue analogs and polyanion compounds. From the perspective of electrochemical performance: layered transition metal oxides have high energy density and good cycle stability, but there may be certain limitations in high rate performance; polyanion compounds have good capacity and cycle stability, but the conductivity and rate performance may need to be further optimized; Prussian blue analogs have three-dimensional fast sodium ion deintercalation channels and high working voltage (>3.4V), excellent rate performance and cycle stability, and are sodium battery positive electrode materials with high industrialization prospects. From the perspective of manufacturing cost, layered transition metal oxides are usually expensive due to the use of rare metals; polyanion compounds involve spray drying, high-temperature sintering and other processes in the synthesis process, and the manufacturing cost is medium; Prussian blue analogs are prepared by co-precipitation process, do not require high-temperature sintering, and have relatively low manufacturing costs, which are suitable for large-scale production. Therefore, considering the electrochemical performance and manufacturing cost, if a low-cost and long-life sodium ion battery system is to be achieved, Prussian blue material is the only choice.

[0004] Conventional sodium-ion battery negative electrode materials use hard carbon and soft carbon. Carbon-based negative electrodes have problems such as low first coulombic efficiency, poor rate performance, and insufficient cycle stability due to the rupture and growth of SEI film. Titanium-based materials use the change between trivalent and tetravalent Ti ions to embed and extract sodium ions. Due to the influence of the electronegativity of different anion groups, the electrochemical potential of titanium-based materials is generally greater than 0.2V, so there will be no SEI film formation. For example, the potential of sodium titanium phosphate relative to sodium is 2.1 V. At this potential, sodium titanium phosphate does not produce SEI film, and it is an ion de-embedding material itself, so there will be no dendrite problem. The test process also found that sodium titanium phosphate has good cycle stability, with only a decay of 0.5% after 1,000 cycles, which meets the requirements of long service life of energy storage power stations (10-15 years).

[0005] Electrolyte is the "blood" in the battery, which plays the role of connecting positive and negative electrode materials and ion transfer, and needs to be fully compatible with positive and negative electrode materials. However, when the Prussian blue analog positive electrode is used in conjunction with a liquid electrolyte, the structure is often degraded due to the dissolution of metal ions, which in turn leads to problems such as rapid capacity decay and short cycle life; although replacing traditional liquid electrolytes with all-solid-state electrolytes is the ultimate solution to the above problems, it is currently difficult to directly meet current needs. Therefore, it is urgent to explore negative electrode materials and new electrolytes that are suitable for Prussian blue materials and to build sodium-ion batteries with stable electrochemical systems. Summary of the invention

[0006] To solve the above problems, the present invention provides a sodium ion energy storage battery. Starting from the top-level design of R&D design and mass production, suitable positive and negative electrode materials are selected and matching electrolytes are designed, so that the electrochemical system achieves the characteristics of low cost, long life and high safety, and has the prospect of commercial-scale production, which can realize the long-life cycle and mass production of sodium ion batteries.

[0007] The present invention provides a sodium ion energy storage battery, the sodium ion energy storage battery comprising:

[0008] A positive electrode sheet, wherein the positive electrode sheet contains a positive electrode active material, and the positive electrode active material includes a Prussian blue material;

[0009] A negative electrode plate, wherein the negative electrode plate contains a negative electrode active material, and the negative electrode active material includes a titanium-based material;

[0010] A gel electrolyte, wherein the gel electrolyte contains an electrolyte and an electrolyte carrier, wherein the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer; wherein the inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded on the sodium titanium phosphate carrier, and the metal salt contains an iron salt.

[0011] The present invention proposes a sodium ion energy storage battery and a preparation method thereof, wherein the battery has an optimal capacity retention rate of more than 97% after 5,000 cycles at a rate of 2C, and a capacity utilization rate of more than 85% at a high rate of 10C. The battery positive and negative active materials and electrolyte preparation processes of the present invention are simple, and the raw material resources are abundant. It has the characteristics of "low cost, high safety, and long life", while ensuring the utilization of its high power advantage, and significantly improving the application value of the sodium ion energy storage battery in practical applications.

[0012] Furthermore, the Prussian blue material conforms to the general formula Na b M1 d M2 c [Fe(CN)6]·mH2O, 0<b≤2, 0≤d≤1, 0≤c<1, c+d=1, 0<m≤3, wherein M1 is selected from one or more of manganese, iron, cobalt and nickel, and M2 is selected from zinc and / or copper.

[0013] Furthermore, the metal salt includes iron salt and M1 metal salt; the M1 metal salt is a salt of at least one metal in M1. The metal salt includes but is not limited to nitrate, hydrochloride and the like.

[0014] Furthermore, the titanium-based material includes at least one of a titanium-based polyanion-type negative electrode material, a titanium-based oxide-type negative electrode material, and a titanium-based spinel-type negative electrode material. Among them, the titanium-based polyanion-type negative electrode material includes polyanion-type NaTi2(PO4)3, Na3MnTi(PO4)3, etc. with a sodium storage potential of 2.1V, and the titanium-based oxide-type negative electrode material includes Na2Ti3O7 with a layered structure and a sodium storage potential of 0.3V, Na 0.66 [Li 0.22 Ti 0.78 ]O2, layered structure with a sodium storage potential of 0.8V Na 0.6 [Cr 0.6 Ti 0.4 ]O2, etc. Titanium-based spinel negative electrode materials include Li4Ti5O with a spinel structure and a sodium storage potential of 0.9V 12 wait.

[0015] Furthermore, in the gel electrolyte, the electrolyte carrier is prepared from a polymer monomer, an initiator, an organic solvent, and an inorganic filler. Taking the total mass of the electrolyte carrier as 100%, the mass percentage of the organic solvent in the electrolyte carrier is 75%-95%, the mass percentage of the inorganic filler in the electrolyte carrier is 0.1%-2%, the mass percentage of the polymer monomer in the electrolyte carrier is 5%-25%, and the mass percentage of the initiator in the electrolyte carrier is 0.01%-0.5%.

[0016] Furthermore, the mass percentage of the organic solvent to the electrolyte carrier is 75%-95%, for example, 75.5%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, etc., including but not limited to the proportions listed above.

[0017] Furthermore, the mass percentage of the polymer monomer to the electrolyte carrier is 5%-25%, for example, 5.5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc., including but not limited to the proportions listed above.

[0018] Furthermore, the mass percentage of the inorganic filler to the electrolyte carrier is 0.1%-2%, for example, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.95%, 1.99%, etc., including but not limited to the proportions listed above.

[0019] Furthermore, the mass percentage of the initiator to the electrolyte carrier is 0.01%-0.5%, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.13%, 0.15%, 0.18%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, etc., including but not limited to the proportions listed above.

[0020] Furthermore, the organic solvent is a carbonate organic solvent, including but not limited to any one or more of propylene carbonate, ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate.

[0021] Furthermore, the polymer monomers forming the polymer include one or more of acrylate, ethylene glycol dimethacrylate, pentaerythritol tetraacrylate, and dioxolane.

[0022] Furthermore, the initiator includes any one or more of boron trifluoride, aluminum trifluoromethanesulfonate, azobisisobutyronitrile, etc.

[0023] Furthermore, the preparation method of the sodium titanium phosphate carrier includes: mixing a titanium source, a sodium source and a phosphorus source to obtain a sodium titanium phosphate precursor, and heat-treating the sodium titanium phosphate precursor to obtain the sodium titanium phosphate carrier; wherein the heat treatment temperature is not less than 700°C.

[0024] Furthermore, the molar ratio of the titanium source, the sodium source and the phosphorus source is (1.9-2.1):1:(2.3-3). That is, they are mixed according to the molar ratio required for sodium titanium phosphate, such as 1.95:1:2.4, 1.9:1:2.5, 1.95:1:2.8, 2:1:2.3, 2:1:2.4, 2:1:2.5, 2:1:2.6, 2:1:2.7, 2:1:2.8, 2:1:2.9, 2:1:3, 2.1:1:2.5, 2.1:1:2.7, 2.1:1:2.8, 2.1:1:2.9, 2.1:1:3, etc., including but not limited to the ratios listed above.

[0025] Furthermore, the temperature of the heat treatment is 700-1200°C, for example, 750°C, 790°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1110°C, 1150°C, 1180°C, 1190°C, etc., including but not limited to the temperatures listed above.

[0026] Furthermore, the heat treatment time is 0.5-10 hours, for example, 0.8 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 9.5 hours, etc., including but not limited to the time lengths listed above.

[0027] Furthermore, the method of loading the metal salt into the sodium titanium phosphate carrier includes dispersing the sodium titanium phosphate carrier and the metal salt in a solvent, and then drying.

[0028] Furthermore, the solvent is a solvent that can dissolve metal salts.

[0029] Furthermore, in the inorganic filler, the molar ratio of the sodium titanium phosphate carrier to the metal salt is 1:(0.5-5), for example 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:4.8, etc., including but not limited to the ratios listed above.

[0030] Further, the electrolyte is a sodium salt, including but not limited to one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(oxalatodi)borate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl imide) and sodium bis(fluorosulfonyl imide). The concentration (molar concentration) of the sodium salt is 0.1 M-10 M; preferably 0.5 M-3.0 M; more preferably 1.0 M.

[0031] Another object of the present invention is to provide a gel electrolyte, wherein the gel electrolyte contains an electrolyte and an electrolyte carrier, wherein the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer;

[0032] The inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded on the sodium titanium phosphate carrier, and the metal salt contains an iron salt.

[0033] Furthermore, the preparation method of the above-mentioned gel electrolyte comprises the following steps:

[0034] The electrolyte, polymer monomer, initiator, organic solvent and inorganic filler are mixed, and the mixture is subjected to a heating treatment to polymerize the mixture to obtain the gel electrolyte.

[0035] Another object of the present invention is to provide a sodium ion battery, which contains the above-mentioned gel electrolyte.

[0036] Furthermore, the positive electrode active materials used include but are not limited to layered transition metal oxides, Prussian blue analogs, polyanion compounds, etc., and the negative electrode active materials include but are not limited to titanium-based materials, carbon-based materials, etc. Of course, it is most preferred that the negative electrode active material is a titanium-based material and the positive electrode active material is a Prussian blue compound.

[0037] Furthermore, the preparation method of the above sodium ion battery comprises the following steps:

[0038] The electrolyte is mixed with an organic solvent, a polymer monomer, an initiator and an inorganic filler to obtain a gel electrolyte precursor solution, and the gel electrolyte precursor solution is injected into a battery containing a positive electrode and a negative electrode, and thermal initiation is used to cause in-situ polymerization to obtain the sodium ion battery.

[0039] Beneficial effects of the present invention:

[0040] The present invention successfully designs a low-cost, green and safe sodium ion energy storage battery by selecting suitable positive and negative active materials and successfully designing a coordinated cross-linked gel polymer electrolyte. The design of the gel polymer electrolyte helps to limit the activity of the solvent and inhibit the side reaction between the electrode and the plasticizer. In addition, by combining with a bifunctional inorganic filler, an organic / inorganic composite sodium ion transmission channel is constructed, realizing Na + The synergistic transport makes the Prussian analog-based sodium-ion battery assembled based on this gel polymer electrolyte exhibit excellent rate and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The charge and discharge curves of the battery system constructed with the material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0043] As described in the background technology, there is currently a lack of overall design for battery systems using Prussian blue as the positive electrode material, especially in the selection and design of suitable negative electrode materials and electrolytes. The present invention takes into account the limitations of current liquid electrolytes and solid electrolytes, attempts to select a gel electrolyte system as the basis for optimization and improvement, and proposes a gel polymer electrolyte with a sodium titanium phosphate carrier loaded with metal salts as a filler, which can not only inhibit the release of metal ions from the Prussian blue positive electrode, but also provide more sodium ions, improve ionic conductivity and ion migration number, and at the same time, the loading structure of sodium titanium phosphate and metal salts overcomes the disordered distribution state of metal salts during the preparation of the electrolyte, which is conducive to the above-mentioned effects. These aspects cooperate with each other to improve the cycle stability and rate performance of any battery system using the gel electrolyte. On this basis, we further optimized and screened the negative electrode and found that when titanium-based materials are used as negative electrodes, they exhibit better performance than other types of negative electrodes (such as carbon-based negative electrodes). Specifically:

[0044] The present invention provides a sodium ion energy storage battery, the sodium ion energy storage battery comprising:

[0045] A positive electrode sheet, wherein the positive electrode sheet contains a positive electrode active material, and the positive electrode active material includes a Prussian blue material;

[0046] A negative electrode plate, wherein the negative electrode plate contains a negative electrode active material, and the negative electrode active material includes a titanium-based material;

[0047] A gel electrolyte, wherein the gel electrolyte contains an electrolyte and an electrolyte carrier, wherein the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer; wherein the inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded on the sodium titanium phosphate carrier, and the metal salt contains an iron salt.

[0048] The battery system of the present invention realizes the technical requirements of "low cost, long life and high safety" of sodium ion energy storage batteries:

[0049] (1) Long-life cycle, stable battery positive and negative electrode materials are the basis: only when the material itself has a stable lattice structure, there is no structural collapse in the electrochemical reaction, and the volume effect is small, can long cycles be achieved in theory. This is the basic requirement for the selection of positive and negative electrode materials in the present invention, and it is also one of the reasons for selecting Prussian blue materials as positive electrodes and titanium-based materials as negative electrodes based on this requirement. Specifically: the preparation process of Prussian blue materials is a co-precipitation method, which does not involve high-energy drying and sintering processes, laying the foundation for large-scale "low-cost" preparation; sodium titanium phosphate in titanium-based materials is an ion deintercalation reaction, and the potential relative to sodium is 2.1 V, so there is no "growth-rupture-reconstruction" of SEI and the appearance of sodium dendrites;

[0050] (2) On the design concept of gel electrolytes: Gel polymer electrolytes represent an excellent balance, combining the advantages of high ionic conductivity, low interfacial impedance, high thermal stability and flexibility. Compared with traditional liquid electrolytes, gel polymer electrolytes are considered to be a promising strategy to replace liquid electrolytes and achieve long-term cycling of sodium-ion batteries due to their excellent mechanical strength, thermal stability, extremely low volatility and high chemical / electrochemical stability. Gel polymer electrolytes are an intermediate state between liquid and solid electrolytes, and the liquid component wrapped by the polymer network forms a gel state. Therefore, the mobility of the liquid plasticizer is limited, which helps to inhibit the interphase side reactions and enhance the interfacial stability. At present, the research on gel polymer electrolytes mainly focuses on inhibiting the formation of dendrites on sodium metal and enhancing the interfacial stability, and significant progress has been made. However, for battery systems without sodium dendrites, the focus of electrolyte design shifts to high compatibility with positive and negative active materials and high ionic conductivity. Due to its unique structural characteristics, the transport of sodium ions in gel polymer electrolytes is no longer dominated by the liquid phase, but occurs in the swollen gel phase or liquid phase. The fluidity of the polymer chain segments also determines the mobility of sodium ions to a certain extent, resulting in significant differences in ionic conductivity and interfacial compatibility between gel polymer electrolytes and liquid electrolytes. How to further improve the ionic conductivity and sodium ion migration number through the structural design optimization of the gel polymer electrolyte so that it meets the cycle stability and high rate requirements of the sodium ion battery positive electrode material is the key technology to achieve the "long life" of the sodium ion energy storage battery of the present invention;

[0051] The present invention adopts a polymerization method combined with a bifunctional inorganic filler as an anchor point, which has the following advantages: a) due to the restriction of the long-chain polymer skeleton on the activity of the solvent, the polymer skeleton limits the mobility of the solvent molecules, constructs a high-quality polymer network, and realizes a highly compatible electrode / electrolyte interface and an organic / inorganic composite sodium ion conduction path; b) the bifunctional inorganic filler integrates components with good compatibility with the polymer skeleton, reduces the crosslinking and crystallinity of the polymer, and accelerates the Na + transmission, and exhibits good mechanical strength and thermal stability, which is conducive to the sodium-ion energy storage battery to achieve better rate performance;

[0052] The electrolyte proposed by the present invention is simple to prepare and the raw materials are easy to obtain. It replaces the traditional carbonate electrolyte and effectively constructs a three-dimensional cross-linked network, which reduces the activity of the solvent, makes the electrolyte have excellent chemical and electrochemical stability, reduces the side reaction of the Prussian analog catalyzing the decomposition of the liquid electrolyte, and improves the interface stability of the Prussian blue analog positive electrode, which adds another guarantee for "long cycle";

[0053] In addition, the gel electrolyte prepared by polymerization method is formed into a gel state by liquid components wrapped by polymer network. Due to the high thermal stability of polymer network, the safety of battery is further improved. It is reflected in the fact that there is no risk of thermal runaway in single battery, which fundamentally solves the "safety" problem of energy storage technology (both active materials and electrolytes);

[0054] (3) Another advantage of the battery system of the present invention lies in the coordination of the positive and negative electrodes and the electrolyte. Compared with other types of positive electrodes (such as layered oxides) or other types of negative electrodes (such as carbon-based materials), the battery system of the present invention uses Prussian blue and titanium-based materials as positive and negative electrodes, and has significantly better cycle stability and rate performance. In particular, when the negative electrode is a polyanion type in the titanium-based material, its performance is optimal, which may be attributed to the organic synergy between the positive and negative electrodes and the electrolyte.

[0055] Preferably, the Prussian blue material conforms to the general formula Na b M1 d M2 c [Fe(CN)6]·mH2O, 0<b≤2, 0≤d≤1, 0≤c<1, c+d=1, 0<m≤3, wherein M1 is selected from one or more of manganese, iron, cobalt, and nickel, and M2 is selected from zinc and / or copper. When Prussian blue is selected as the positive electrode material, the iron element will inevitably be released during the use of the battery, so the battery system needs to be designed to alleviate the dissolution of iron in Prussian blue.

[0056] More preferably, the metal salt includes an iron salt and an M1 metal salt; the M1 metal salt is a salt of at least one metal in M1. If the Prussian blue material involves transition metal M1, there may be a certain degree of dissolution. Designing a battery system to alleviate the dissolution of transition metals in Prussian blue can further improve battery performance.

[0057] Among them, the inorganic iron salt / transition metal salt includes but is not limited to nitrate or hydrochloride, such as Fe(NO3)3, FeCl3, M1 (NO3)2, M1Cl2, M1 is one of Mn, Fe, Co, and Ni.

[0058] Preferably, the titanium-based material includes at least one of a titanium-based polyanion-type negative electrode material, a titanium-based oxide-type negative electrode material, and a titanium-based spinel-type negative electrode material. Among them, the titanium-based polyanion-type negative electrode material includes polyanion-type NaTi2(PO4)3, Na3MnTi(PO4)3, etc. with a sodium storage potential of 2.1V, and the titanium-based oxide-type negative electrode material includes Na2Ti3O7 with a layered structure and a sodium storage potential of 0.3V, Na 0.66 [Li 0.22 Ti 0.78]O2, layered structure with a sodium storage potential of 0.8V Na 0.6 [Cr 0.6 Ti 0.4 ]O2, etc. Titanium-based spinel negative electrode materials include Li4Ti5O with a spinel structure and a sodium storage potential of 0.9V 12 The most preferred is a titanium-based polyanion negative electrode material, which has no obvious collapse during the cycle and has a certain synergistic effect with the positive electrode and the electrolyte, and has the best performance.

[0059] Preferably, in the gel electrolyte, the electrolyte carrier is prepared from a polymer monomer, an initiator, an organic solvent and an inorganic filler. Taking the total mass of the electrolyte carrier as 100%, the mass percentage of the organic solvent in the electrolyte carrier is 75%-95%, the mass percentage of the inorganic filler in the electrolyte carrier is 0.1%-2%, the mass percentage of the polymer monomer in the electrolyte carrier is 5%-25%, and the mass percentage of the initiator in the electrolyte carrier is 0.01%-0.5%.

[0060] The mass percentage of the organic solvent to the electrolyte carrier is 75%-95%, for example 75.5%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, etc., including but not limited to the proportions listed above, and most preferably 80%-90%.

[0061] The mass percentage of the polymer monomer to the electrolyte carrier is 5%-25%, for example 5.5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc., including but not limited to the proportions listed above, and most preferably 10%-20%.

[0062] The mass percentage of the inorganic filler in the electrolyte carrier is 0.1%-2%, such as 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.95%, 1.99%, etc., including but not limited to the proportions listed above, and most preferably 1%. When the mass fraction of the bifunctional inorganic filler exceeds a certain proportion (such as 2%), as the mass fraction increases, during the in-situ polymerization process, the polymer monomer may no longer be able to form a continuous network structure, which deviates from the original intention of the gel electrolyte design-the gel polymer electrolyte is an intermediate state between a liquid and a solid electrolyte, and the liquid component wrapped by the polymer network forms a gel state. At this time, the performance of the electrolyte is more inclined to that of a liquid electrolyte, and the battery rate performance will be reduced due to the addition of excessive inorganic fillers to hinder ion conduction.

[0063] The mass percentage of the initiator to the electrolyte carrier is 0.01%-0.5%, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.13%, 0.15%, 0.18%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, etc., including but not limited to the proportions listed above, and most preferably 0.05%-0.3%.

[0064] Preferably, the organic solvent is a carbonate organic solvent, including but not limited to any one or more of propylene carbonate, ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate.

[0065] Preferably, the polymer monomers forming the polymer include one or more of acrylate (such as methyl acrylate, ethyl acrylate), ethylene glycol dimethacrylate, pentaerythritol tetraacrylate, and dioxolane.

[0066] Preferably, the initiator includes any one or more of boron trifluoride, aluminum trifluoromethanesulfonate, azobisisobutyronitrile, and the like.

[0067] Preferably, the preparation method of the sodium titanium phosphate carrier comprises: mixing a titanium source, a sodium source and a phosphorus source to obtain a sodium titanium phosphate precursor, and heat-treating the sodium titanium phosphate precursor to obtain the sodium titanium phosphate carrier; wherein the temperature of the heat treatment is not less than 700° C. The sodium titanium phosphate carrier obtained by the preparation method of the present invention has a microscopic morphology that can adsorb metal salts. The metal salts are loaded in this way and added to the gel electrolyte, so that the release of the metal salts is controllable and appropriate, which helps to improve the battery performance.

[0068] In the above preparation process, the molar ratio of the titanium source, the sodium source and the phosphorus source is (1.9-2.1):1:(2.3-3). That is, they are mixed according to the molar ratio required for sodium titanium phosphate, such as 1.95:1:2.4, 1.9:1:2.5, 1.95:1:2.8, 2:1:2.3, 2:1:2.4, 2:1:2.5, 2:1:2.6, 2:1:2.7, 2:1:2.8, 2:1:2.9, 2:1:3, 2.1:1:2.5, 2.1:1:2.7, 2.1:1:2.8, 2.1:1:2.9, 2.1:1:3, etc., including but not limited to the ratios listed above.

[0069] Preferably, the heat treatment temperature is 700-1200°C, such as 750°C, 790°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1110°C, 1150°C, 1180°C, 1190°C, etc., including but not limited to the temperatures listed above. The most preferred temperature is 800°C.

[0070] Preferably, the heat treatment time is 0.5-10 hours, such as 0.8 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 9.5 hours, etc., including but not limited to the time lengths listed above. Most preferably, it is 2 hours.

[0071] Preferably, the method of loading the metal salt in the sodium titanium phosphate carrier includes dispersing the sodium titanium phosphate carrier and the metal salt in a solvent and then drying; in the inorganic filler, the molar ratio of the sodium titanium phosphate carrier to the metal salt is 1: (0.5-5). For example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:4.8, etc., including but not limited to the ratios listed above. The most preferred ratio is 1:0.5-3.

[0072] Preferably, the electrolyte is a sodium salt, including but not limited to one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(oxalatodi)borate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl imide) and sodium bis(fluorosulfonyl imide). The concentration (molar concentration) of the sodium salt is 0.1 M-10 M; preferably 0.5 M-3.0 M; more preferably 1.0 M.

[0073] Specifically, the preparation method of the inorganic filler is preferably:

[0074] ① The titanium source, sodium source and phosphorus source are mixed evenly according to the molar ratio of titanium, sodium and phosphate (1.9-2.1): 1: (2.3-3), and the mixture is ball-milled at 500-1500r / min for 5-10 h in a stirring ball mill. The mixed raw materials are spray-dried at 100-200°C, and the obtained powder is heat-treated at a heating temperature of 700°C-1200°C for a heating time of 30min-10h to obtain an NTP carrier;

[0075] ② The NTP carrier and the metal salt prepared in the above step are dispersed in a solvent at a molar ratio of 1:0.5-1:5, mixed evenly, and dried to obtain a precipitate.

[0076] Preferably, the solvent is a solvent that can dissolve the metal salt.

[0077] In the battery system of the present invention, the active layer of the positive electrode plate further includes a conductive agent and a binder, and the active layer of the negative electrode plate further includes a conductive agent and a binder.

[0078] Preferably, the positive electrode active layer comprises a positive electrode active material, a conductive agent and a binder. The positive electrode active layer comprises the following components by mass percentage: 75-95% of the positive electrode active material, 5-15% of the conductive agent and 5-15% of the binder. Preferably, the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder. The negative electrode active layer comprises the following components by mass percentage: 75-95% of the negative electrode active material, 5-15% of the conductive agent and 5-15% of the binder.

[0079] The conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene, Ketjen black, and acetylene black.

[0080] Preferably, the binder is a binder well known to those skilled in the art, without any particular limitation, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF is selected.

[0081] Preferably, the thickness of the positive electrode active layer or the negative electrode active layer is in the range of 100-300 μm, for example, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, etc., including but not limited to the thickness values ​​listed above.

[0082] The embodiment of the present invention also provides a method for preparing a gel electrolyte, comprising the following steps:

[0083] The electrolyte, polymer monomer, initiator, organic solvent and inorganic filler are mixed, and the mixture is subjected to a heating treatment to polymerize the mixture to obtain the gel electrolyte.

[0084] The gel electrolyte prepared by the above preparation method contains an electrolyte and an electrolyte carrier, wherein the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer; wherein the inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded in the sodium titanium phosphate carrier, and the metal salt contains an iron salt. The polymer, the organic solvent and the inorganic filler mentioned are the same as above.

[0085] The present invention also provides a sodium ion battery, which contains the above-mentioned gel electrolyte. At this time, the positive electrode active material and the negative electrode active material used can be any material commonly used in the field of battery technology. After experimental verification, when the types of positive electrode active materials and negative electrode active materials are replaced, such as the positive electrode active material is a layered oxide, and the negative electrode active material is a titanium-based material or a carbon-based material, the performance is significantly improved compared to the battery system that does not use the gel electrolyte of the present invention. This shows the advantages of the gel electrolyte of the present invention as a battery electrolyte. Of course, it is most preferred that the negative electrode is a titanium-based material and the positive electrode is a Prussian blue compound.

[0086] The present invention provides a method for preparing a sodium ion battery, comprising the following steps:

[0087] The electrolyte is mixed with an organic solvent, a polymer monomer, an initiator and an inorganic filler to obtain a gel electrolyte precursor solution, and the gel electrolyte precursor solution is injected into a battery containing a positive electrode and a negative electrode, and thermal initiation is used to cause in-situ polymerization to obtain the sodium ion battery.

[0088] Preferably, the method for preparing the battery comprises:

[0089] ① The positive and negative active materials and the conductive agent are mixed evenly, pressed into positive and negative electrodes by coating rollers, and stacked into single cells;

[0090] ② Adding sodium salt into carbonate organic solvent to form liquid electrolyte A;

[0091] ③ Add polymer monomer, initiator and bifunctional inorganic filler to liquid electrolyte A, stir evenly to prepare precursor B of gel electrolyte;

[0092] ④ Inject the precursor B of the gel electrolyte into the assembled single cell;

[0093] ⑤ The single cell is heated between 60 and 100 °C for 30 min to 6 h, and the precursor B of the gel electrolyte undergoes in-situ polymerization to obtain a sodium ion energy storage battery.

[0094] In-situ polymerization is preferred because it combines the advantages of liquid electrolyte and polymer electrolyte, achieving high ionic conductivity and good interface contact. At the same time, thermal polymerization through high temperature is also the easiest technology to achieve mass production. At the same time, since the liquid part of the in-situ polymerized electrolyte has high ion diffusivity, it can make the bifunctional inorganic filler play a role. Example 1

[0095] A sodium ion energy storage battery, the preparation steps are as follows:

[0096] (1) Preparation of bifunctional inorganic fillers:

[0097] ① A certain proportion of titanium dioxide, sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate were uniformly mixed by mechanical stirring, titanium source and sodium source were added according to the molar ratio of titanium to sodium of 2:1, and phosphorus source was added according to the molar ratio of phosphate to sodium of 2.5:1; a stirring ball mill was used for ball milling at 1000r / min for 7 hours, the mixed raw materials were spray dried at 150°C, and the obtained powder was heat treated at a heating temperature of 800°C for 2 hours to obtain a sodium titanium phosphate carrier (NTP);

[0098] ② Disperse the granular powder prepared in the above steps and Fe(NO3)3 and Mn(NO3)2 in ethanol at a molar ratio of 1:1, mix them evenly, and dry them to obtain a precipitate, which is a bifunctional inorganic filler.

[0099] (2) Preparation of electrolyte precursor:

[0100] ① Sodium hexafluorophosphate is added to propylene carbonate solvent to form a liquid electrolyte;

[0101] ② Add ethylene glycol dimethacrylate, isopentaerythritol tetraacrylate, azobisisobutyronitrile and the bifunctional inorganic filler prepared above into the liquid electrolyte, stir evenly to prepare a precursor of the gel electrolyte.

[0102] In the above preparation process, sodium hexafluorophosphate is used as the electrolyte, and the concentration of sodium hexafluorophosphate is 1 M. The electrolyte carrier is composed of a carbonate organic solvent, a bifunctional inorganic filler, a polymer monomer and an initiator. In the electrolyte carrier, the mass fraction of the carbonate organic solvent is 84.551%, the mass fraction of the bifunctional inorganic filler is 1%, the molar ratio NTP: (Mn(NO3)2+Fe(NO3)3)=1:1, the molar ratio of Mn(NO3)2 and Fe(NO3)3 is 1:1, the mass fractions of the polymer monomers ethylene glycol dimethacrylate and isopentaerythritol tetraacrylate are 9.4% and 4.95%, respectively, and the mass fraction of the initiator azobisisobutyronitrile is 0.099%.

[0103] (3) Preparation of batteries:

[0104] Pole coating: 80% of the Prussian analogue positive electrode material Na 1.7 Mn 0.8 Cu 0.2 The slurry of [Fe(CN)6]·2.7H2O / sodium titanium phosphate negative electrode material, 10% super P and 10% polyvinylidene fluoride was coated on aluminum foil to prepare the Prussian analog positive electrode / sodium titanium phosphate negative electrode. After drying at 100℃ for 10 h, the electrode film was punched into a pole piece with a diameter of 14 mm. The mass loading of active material was about 2.5 mg·cm -2 .

[0105] Assembling sodium ion battery: In a glove box filled with argon, assemble the battery with a 9 μm thick PE (polyethylene) separator, the electrolyte precursor prepared above, the positive electrode plate and the negative electrode plate. Inject 60 μL of the precursor solution of the above gel polymer electrolyte (GPE) into the PE separator, load it into a CR2032 button cell, seal the battery with a crimping machine, and place the battery in an oven at 70°C for 3 hours after standing for 3 hours. The precursor solution is in situ polymerized under thermal initiation conditions to form a gel polymer electrolyte to obtain a sodium ion energy storage battery. Example 2

[0106] Replace the negative electrode material sodium titanium phosphate NaTi2(PO4)3 with Na2Ti3O7, Na 0.66 [Li 0.22 Ti 0.78 ]O2, Na3MnTi(PO4)3, Li4Ti5O 12 Or Na 0.6 [Cr 0.6 Ti0.4]O2, and the rest of the operations are the same as in Example 1. Example 3

[0107] The proportion of the bifunctional inorganic filler was adjusted to 2%, and the mass fraction of the carbonate organic solvent was adjusted to 83.551%. The remaining operations were the same as in Example 1. Example 4

[0108] The proportion of the bifunctional inorganic filler was adjusted to 0.5%, and the mass fraction of the carbonate organic solvent was adjusted to 85.051%. The remaining operations were the same as in Example 1. Example 5

[0109] NTP and Fe(NO3)3, Mn(NO3)2 are dispersed in ethanol at a molar ratio of NTP: (Fe(NO3)3+Mn(NO3)2) = 1:0.5, and the remaining operations are the same as in Example 1. Example 6

[0110] NTP and Fe(NO3)3, Mn(NO3)2 are dispersed in ethanol at a molar ratio of NTP: (Fe(NO3)3+Mn(NO3)2) = 1:3, and the remaining operations are the same as in Example 1. Example 7

[0111] NTP and Fe(NO3)3, Mn(NO3)2 are dispersed in ethanol at a molar ratio of NTP: (Fe(NO3)3+Mn(NO3)2) = 1:5, and the remaining operations are the same as in Example 1. Example 8

[0112] The carbonate organic solvent was replaced with fluoroethylene carbonate, the polymer monomer was replaced with dioxolane, the proportion of the bifunctional inorganic filler was adjusted to 0.1%, the proportion of fluoroethylene carbonate was adjusted to 78.1%, the proportion of dioxolane was adjusted to 21.55%, the mass fraction of the initiator azobisisobutyronitrile was adjusted to 0.25%, sodium perchlorate was used as the electrolyte with a concentration of 3.0 M, and the remaining operations were the same as in Example 1. Example 9

[0113] The heat treatment temperature in step (1) ① was adjusted to 700° C., the heating time was adjusted to 4 h, and the remaining operations were the same as in Example 1. Example 10

[0114] The heat treatment temperature in step (1) ① is adjusted to 1200° C., the heating time is still 2 h, and the remaining operations are the same as in Example 1. Embodiment 11

[0115] A sodium ion energy storage battery, the preparation steps are as follows:

[0116] (1) Preparation of bifunctional inorganic fillers:

[0117] ① A certain proportion of titanium dioxide, sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate were uniformly mixed by mechanical stirring, titanium source and sodium source were added according to the molar ratio of titanium to sodium of 1.9:1, and phosphorus source was added according to the molar ratio of phosphate to sodium of 3:1; a stirring ball mill was used for ball milling at 1500r / min for 5 h, the mixed raw materials were spray dried at 100°C, and the obtained powder was heat treated at a heating temperature of 750°C for a heating time of 1.5 h to obtain a sodium titanium phosphate carrier (NTP);

[0118] ② Disperse the granular powder prepared in the above steps and Fe(NO3)3 and Ni(NO3)2 in ethanol at a molar ratio of 1:1, mix them evenly, and dry them to obtain a precipitate, which is a bifunctional inorganic filler.

[0119] (2) Preparation of electrolyte precursor:

[0120] ① Sodium hexafluorophosphate is added to dimethyl carbonate solvent to form a liquid electrolyte;

[0121] ② Add methyl acrylate, azobisisobutyronitrile and the bifunctional inorganic filler prepared above into the liquid electrolyte, stir evenly to prepare a precursor of the gel electrolyte.

[0122] In the above preparation process, sodium hexafluorophosphate is used as the electrolyte, and the concentration of sodium hexafluorophosphate is 1 M. The electrolyte carrier is composed of a carbonate organic solvent, a bifunctional inorganic filler, a polymer monomer and an initiator. In the electrolyte carrier, the mass fraction of the carbonate organic solvent is 93.99%, the mass fraction of the bifunctional inorganic filler is 1%, the molar ratio NTP: (Ni(NO3)2+Fe(NO3)3)=1:1, the molar ratio of Ni(NO3)2 and Fe(NO3)3 is 1:1, the mass fraction of the polymer monomer methyl acrylate is 5%, and the mass fraction of the initiator azobisisobutyronitrile is 0.01%.

[0123] (3) Preparation of batteries:

[0124] Pole sheet coating: A slurry containing 80% of the Prussian analogue positive electrode material Na2Ni[Fe(CN)6] ·1.8H2O / sodium titanium phosphate negative electrode material, 10% super P and 10% polyvinylidene fluoride was coated on aluminum foil to prepare the Prussian analogue positive electrode / sodium titanium phosphate negative electrode. After drying at 100°C for 10 h, the electrode film was punched into a pole sheet with a diameter of 14 mm. The mass loading of the active material was about 2.5 mg·cm -2 .

[0125] Assembling sodium ion battery: In a glove box filled with argon, assemble the battery with a 9 μm thick PE (polyethylene) separator, the electrolyte precursor prepared above, the positive electrode plate and the negative electrode plate. Inject 60 μL of the precursor solution of the above gel polymer electrolyte (GPE) into the PE separator, load it into a CR2032 button cell, seal the battery with a crimping machine, and after standing for 3 hours, place the battery in an oven at 100°C and heat it for 1 hour. The precursor solution is in situ polymerized under thermal initiation conditions to form a gel polymer electrolyte to obtain a sodium ion energy storage battery. Comparative Example 1

[0126] No bifunctional inorganic filler was added, and the rest was the same as in Example 1. Comparative Example 2

[0127] In the bifunctional inorganic filler, NTP does not load Fe(NO3)3 and Mn(NO3)2, and the rest is the same as Example 1. Comparative Example 3

[0128] No NTP is added to the bifunctional inorganic filler, that is, the bifunctional inorganic filler is replaced by a mixture of Fe(NO3)3 and Mn(NO3)2 in a molar ratio of 1:1, and the rest is the same as in Example 1. Comparative Example 4

[0129] A liquid electrolyte was prepared by adding sodium hexafluorophosphate with propylene carbonate as solvent to replace the gel electrolyte in Example 1. The rest was the same as Example 1. Comparative Example 5

[0130] The bifunctional inorganic filler is prepared according to the following method, and the remaining operations are the same as those in Example 1.

[0131] ① A certain proportion of titanium dioxide, sodium dihydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate are uniformly mixed by mechanical stirring, titanium source and sodium source are added according to the molar ratio of titanium to sodium of 2:1, and phosphorus source is added according to the molar ratio of phosphate to sodium of 2.5:1; a stirring ball mill is used for ball milling at 1000r / min for 7 hours, the mixed raw materials are spray dried at 150°C, and the obtained powder is heat treated at a heating temperature of 1000°C for 2 hours to obtain NTP;

[0132] ② The NTP prepared in the above step is uniformly mixed with Fe(NO3)3 and Mn(NO3)2 in a molar ratio of 1:1 to obtain a bifunctional inorganic filler. Comparative Example 6

[0133] The NTP carrier in the bifunctional inorganic filler was replaced with porous silica, and the remaining operations were the same as in Example 1. Comparative Example 7

[0134] The negative electrode was replaced with hard carbon, and the rest was the same as in Example 1. Comparative Example 8

[0135] The negative electrode was replaced with hard carbon, and the gel electrolyte was replaced with a liquid electrolyte (sodium hexafluorophosphate was added with propylene carbonate as solvent), and the rest was the same as in Example 1. Comparative Example 9

[0136] The positive electrode is replaced by layered oxide Na[Ni 0.33 Co 0.33 Mn 0.33 ]O2, and the rest is the same as in Example 1.

[0137] The test process and results are as follows:

[0138] Battery activation: The assembled battery was placed in a 45°C constant temperature box and activated using a Blue Electric charge and discharge instrument. The activation voltage range was 2 to 4 V, the charge and discharge rate was 0.1C, and the charge and discharge were performed for 3 weeks.

[0139] Battery cycle stability test: The activated battery is subjected to a 2C, 5000-cycle cycle stability test, with a charge and discharge voltage range of 2 to 4 V. During the test, the instrument automatically records the charge and discharge data and related curves.

[0140] Battery rate performance test: The activated battery is subjected to constant current charge and discharge tests at 0.1C, 0.5C, 2C, and 10C, and the charge and discharge voltage range is 2 to 4.2 V. During the test, the instrument automatically records the charge and discharge data and related curves.

[0141] The results are shown in Tables 1 and 2.

[0142] Table 1

[0143]

[0144] Table 2

[0145]

[0146]

[0147]

[0148] From Table 1 we can see that:

[0149] The negative electrodes in Example 1 and Example 2 are combined with specific electrolytes and Prussian blue materials, and the batteries have good cycle performance and discharge medium voltage. However, the performance of batteries prepared with different titanium-based materials as negative electrodes is also different: when the negative electrode is a polyanion NaTi2(PO4)3 and Na3MnTi(PO4)3 with a NASICON structure, the 5000-cycle capacity retention rate is greater than 95%; when the negative electrode structure used is a layered oxide, the structure will collapse to a certain extent during the cycle, and the battery attenuation is caused by the negative electrode, but even so, the 5000-cycle retention rate is still greater than 60%; when the negative electrode is a spinel structure Li4Ti5O 12 When , the cycling stability is between that of polyanions and layered oxides.

[0150] From Table 2 we can see that:

[0151] When the electrolyte does not contain a bifunctional inorganic filler (Comparative Example 1), the battery rate performance is reduced due to the absence of excess sodium ions provided by sodium titanium phosphate. Compared with Example 1, the 0.1C specific capacity is reduced by 8%, and the 10C specific capacity is reduced by 33%. When the inorganic filler is only NTP (Comparative Example 2), although the ion migration number of the electrolyte is increased due to the increase in the amount of NTP, the rate performance is improved, but due to the absence of the addition of inorganic salts, the capacity attenuation of the Prussian blue positive electrode material due to the dissolution of metal elements is difficult to be suppressed, and the cycle performance is poor, and its capacity retention rate is only 83.4%; when the bifunctional inorganic filler contains only iron / manganese salts without adding NTP (Comparative Example 3), both the capacity retention rate and the specific capacity are reduced, especially due to the absence of sodium titanium phosphate that provides additional sodium ions, the rate performance is poor; More importantly, even if a carrier is added to the gel electrolyte but it is not added in the form of loaded iron salts and manganese salts (Comparative Example 5), or no specific type of carrier is added (Comparative Example 6), the battery performance will be significantly reduced;

[0152] When the negative electrode is replaced with hard carbon (Comparative Example 7), the cycle retention rate decreases significantly, which may be due to the structural collapse of hard carbon during the cycle. The overall cycle capacity retention rate of the battery is reduced by about 40 percentage points compared with the sodium ion energy storage battery of the present invention. When the positive electrode is a layered oxide (Comparative Example 9), the capacity retention rate decreases due to phase transition and structural collapse during the charge and discharge process. At the same time, due to the layered structure and the lack of a large framework lattice structure, its rate performance is not as good as the sodium ion energy storage battery of the present invention;

[0153] However, regardless of whether hard carbon or sodium titanium phosphate is used as the negative electrode, compared with conventional carbonate electrolytes, the cycle stability can be improved by 100% or more by using the gel electrolyte of the present invention (Comparative Examples 3~4, Comparative Examples 7~8), which shows that the gel electrolyte of the present invention has potential in improving the performance of batteries using Prussian blue as the positive electrode.

[0154] In addition, Table 2 also shows:

[0155] Sodium titanium phosphate NTP in the bifunctional inorganic filler can be used as a sodium ion solid electrolyte. Its addition can not only improve the mechanical strength of the gel electrolyte, but also improve its ion conductivity and ion migration number. The titanium atom has an anion capture effect, which can increase the ion migration number of the cation. Therefore, the rate performance of the battery system prepared by the present invention is significantly improved; the addition of inorganic iron / manganese source can in situ supplement the dissolved transition metal elements during the charge and discharge process of the Prussian analog, and alleviate the capacity decay of the Prussian positive electrode material caused by the dissolution of metal elements; its optimal content is 1%, at which time the sodium ion energy storage battery has a capacity retention rate of up to 97.1%;

[0156] The optimal ratio of sodium titanium phosphate NTP, which promotes sodium ion migration, to iron / manganese salt, which alleviates Prussian blue attenuation, in the bifunctional inorganic filler is 1:1, wherein the ratio of Fe source to Mn source can be any ratio. As the ratio of iron / manganese salt increases, the cycle stability of the battery will not continue to increase. When it is greater than 1:3, the cycle stability and rate performance of the battery system may decrease slightly (but still higher than 90%, Example 7) due to the excessive inorganic salt hindering the polymerization of the monomer.

[0157] It can be seen from Examples 8-10 that, regardless of the change in organic solvent, polymer network, preparation of NTP carrier, type of Prussian blue positive electrode material or preparation temperature, as long as the battery system prepared according to the method of the present invention has good cycle stability and rate performance. And Example 11 also shows that although the powder grains of nickel-based Prussian blue (D50=7.8μm) and manganese-based Prussian blue (D50=2.1μm) are slightly different, the rate performance is also different, but the battery performance prepared by both nickel-based and manganese-based Prussian blue materials is good, indicating that the method of the present invention is applicable to different types of Prussian blue materials.

[0158] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A sodium ion energy storage battery, characterized in that: The sodium ion energy storage battery comprises: A positive electrode sheet, wherein the positive electrode sheet contains a positive electrode active material, and the positive electrode active material includes a Prussian blue material; A negative electrode plate, wherein the negative electrode plate contains a negative electrode active material, and the negative electrode active material includes a titanium-based material; A gel electrolyte, wherein the gel electrolyte contains an electrolyte and an electrolyte carrier, the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer; The inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded on the sodium titanium phosphate carrier, and the metal salt contains an iron salt; The Prussian blue material conforms to the general formula Na b M1 d M2 c [Fe(CN)6]·mH2O, 0<b≤2, 0≤d≤1, 0≤c<1, c+d=1, 0<m≤3, wherein M1 is selected from one or more of manganese, iron, cobalt and nickel, and M2 is selected from zinc and / or copper; The titanium-based material is selected from at least one of a titanium-based polyanion-type negative electrode material, a titanium-based oxide-type negative electrode material, and a titanium-based spinel-type negative electrode material; The organic solvent is a carbonate organic solvent; The polymer monomers forming the polymer are selected from one or more of acrylate, ethylene glycol dimethacrylate, pentaerythritol tetraacrylate, and dioxolane; The method of loading the metal salt on the sodium titanium phosphate carrier comprises the steps of dispersing the sodium titanium phosphate carrier and the metal salt in a solvent and then drying.

2. The sodium ion energy storage battery according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The metal salt includes an iron salt and an M1 metal salt; the M1 metal salt is a salt of at least one metal in M1; (2) The titanium-based polyanion negative electrode material includes at least one of NaTi2(PO4)3 and Na3MnTi(PO4)3; (3) The titanium-based oxide negative electrode material includes Na2Ti3O7, Na 0.66 [Li 0.22 Ti 0.78 ]O2、Na 0.6 [Cr 0.6 Ti 0.4 ] At least one of O2; (4) The titanium-based spinel negative electrode material includes Li4Ti5O 12 .

3. The sodium ion energy storage battery according to claim 1, characterized in that: Taking the total mass of the electrolyte carrier as 100%, the mass percentage of the organic solvent in the electrolyte carrier is 75%-95%, the mass percentage of the inorganic filler in the electrolyte carrier is 0.1%-2%, and the mass percentage of the polymer monomer forming the polymer in the electrolyte carrier is 5%-20%.

4. The sodium ion energy storage battery according to claim 1, characterized in that: The sodium titanium phosphate carrier comprises at least one of the following characteristics: (1) The preparation method of the sodium titanium phosphate carrier comprises: mixing a titanium source, a sodium source and a phosphorus source to obtain a sodium titanium phosphate precursor, and heat-treating the sodium titanium phosphate precursor to obtain the sodium titanium phosphate carrier; wherein the heat treatment temperature is not less than 700°C; (2) The molar ratio of the titanium source, the sodium source and the phosphorus source is (1.9-2.1):1:(2.3-3); (3) The temperature of the heat treatment is 700-1200°C; (4) The heat treatment time is 0.5-10 hours.

5. The sodium ion energy storage battery according to claim 1, characterized in that: In the inorganic filler, the molar ratio of the sodium titanium phosphate carrier to the metal salt is 1:(0.5-5).

6. The sodium ion energy storage battery according to claim 1, characterized in that: The electrolyte is a sodium salt; The sodium salt includes one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(oxalatodi)borate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl imide) and sodium bis(fluorosulfonyl imide).

7. A gel electrolyte, characterized in that: The gel electrolyte contains an electrolyte and an electrolyte carrier, the electrolyte carrier contains a polymer, an organic solvent and an inorganic filler, and the electrolyte, the organic solvent and the inorganic filler are dispersed in the polymer; The inorganic filler contains a sodium titanium phosphate carrier and a metal salt loaded on the sodium titanium phosphate carrier, and the metal salt contains an iron salt; The organic solvent is a carbonate organic solvent; The polymer monomers forming the polymer are selected from one or more of acrylate, ethylene glycol dimethacrylate, pentaerythritol tetraacrylate, and dioxolane; The method of loading the metal salt on the sodium titanium phosphate carrier comprises the steps of dispersing the sodium titanium phosphate carrier and the metal salt in a solvent and then drying.

8. A sodium ion battery, characterized in that: The sodium ion battery contains the gel electrolyte according to claim 7.

9. The method for preparing a sodium ion battery according to claim 8, characterized in that: The following steps are involved: The electrolyte is mixed with an organic solvent, a polymer monomer, an initiator and an inorganic filler to obtain a gel electrolyte precursor solution, and the gel electrolyte precursor solution is injected into a battery containing a positive electrode and a negative electrode, and thermal initiation is used to cause in-situ polymerization to obtain the sodium ion battery.

Citation Information

Patent Citations

  • Electropolymerization gel electrolyte battery and preparation method thereof

    CN116093426A

  • Composite film suitable for Prussian blue positive electrode material and preparation method and application thereof

    CN118703012A